If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(x + 3) = 3(2x + -1) Reorder the terms: 5(3 + x) = 3(2x + -1) (3 * 5 + x * 5) = 3(2x + -1) (15 + 5x) = 3(2x + -1) Reorder the terms: 15 + 5x = 3(-1 + 2x) 15 + 5x = (-1 * 3 + 2x * 3) 15 + 5x = (-3 + 6x) Solving 15 + 5x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 15 + 5x + -6x = -3 + 6x + -6x Combine like terms: 5x + -6x = -1x 15 + -1x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 15 + -1x = -3 + 0 15 + -1x = -3 Add '-15' to each side of the equation. 15 + -15 + -1x = -3 + -15 Combine like terms: 15 + -15 = 0 0 + -1x = -3 + -15 -1x = -3 + -15 Combine like terms: -3 + -15 = -18 -1x = -18 Divide each side by '-1'. x = 18 Simplifying x = 18
| 1a+2=(-9) | | -4x-5[-x+10]=-43 | | 6x-8(x+3)=-14 | | 8x+7x-6x=18 | | i=400*0.0013*2 | | -6x+4[-2x+8]=130 | | x^2+39x+47=0 | | -2+8=5-(10p+4) | | i=400*0.13*2 | | 2x+6[-5x-15]=190 | | 4-3x+8=5x-4 | | 70x^2-53x+9=0 | | 2(x+4)=x-7 | | 26x-14=3 | | -10+3m=2(4m+-5) | | X+50=210 | | 7x+6[-x-17]=-109 | | x+x+(x-45)+(x-45)+(x-45)=540 | | x=28.75+0.25y | | 2(x-1)+x=4+5 | | x=320+.2x | | 4x-y+65=180 | | 4(x+4)=x-7 | | 3x-7[2x+6]=90 | | 3x-1.8=1-x | | 6.9-3v=2.1 | | 2x+2y=65 | | -17(y+3)+6(4y-3)=6(y-5)+9 | | x+5=2(2x-4) | | -5x-5[3x+18]=150 | | 5x+-9=-14 | | 2(x-1)+x=10 |